Apie marginalijas kaip knygų prekybos istorijos šaltinį - Braziūnienė, Alma (Knygotyra, 1995)
Marginalia are the manuscript inscriptions in the books. The investigation of it gives us an interesting material on the prices of the books in the past. The marginalia card-indexes are in the Library of Lithuanian Academy of Science and in the Library of Vilnius University. The marginalia with prices of the books of the 16–18th centuries and Pabrėža’s books collection are analysed. The prices of the books are compared with the prices of milk, corn, oxes etc. These examples show that the books were very expensive and therefore available only for the small part of the society. For example, the priest J. Pabrėža could buy only one book of the 18th century for money got for five Mass held in Kretinga. Only complete description of the funds of the old books in the libraries and the exhaustive card-indexes of marginalia would give the rich material for the history of the book trade in Lithuania.